Sorption of phosphate from acidic wastewater into three tunisian clay soils - Hamdi, N.; Srasra, E. (Химия и технология воды, 2008)
The removal of phosphates from acidic wastewater using three soil minerals (Soil1, Soil2, and Soil3) with high content of paligoskite, smectite and illite, respectively, is studied. The effect of the medium pH value, contact duration and solid:liquid ratio is considered. The smectite-containing soil possesses the highest sorption capacity with respect to phosphate. The isotherms of phosphate sorption by soils are processed in the Freundlich and Langmuir equation coordinates. It is shown that the fitting of isotherms in the Freundlich equation coordinates results in better correspondence with experimental data. In addition, the adsorption selectivity of ions (PO₄³⁻, F⁻, Cl⁻) existing in waste solution by these soils was studied, and the fluoride is more selective at acidic pH region.